1.102. Rozwiąż równania: a) c) e) g) (3x – 4)/2 = (4x – 5)/3 2/(x ^ 2) = 1/3 (3(x – 1))/5 – (x – 3)/2 = (x – 8)/10 (x(x – 1))/4 – (2x ^ 2 + 1)/2 = – 3/4 * x ^ 2 – 0, 25(x + 2) II. (3x – 1)/(x + 2) = 2/3 II. 3x * (x + 2) = 0 II. (x ^ 2 + 2x + 6)/(x ^ 2) = 1 b) d) f) (x ^ 2 – 16)/(x – 4) = 0 III. (x – 4) – (2x – 9) = 0 I. (x ^ 2 – 4)/(x – 2) = 0 (3x – 1)/(x ^ 2 + 1) = 3/x x/2 = 8/x 1/(x – 1) + 2 = 0 (3(x – 11))/4 = (3(x + 1))/5 – (2(2x – 5))/11 (x + (4 – x)/3)/5 = (x – (x – 5)/5)/3 h)

1.102. Rozwiąż równania: a) c) e) g) (3x – 4)/2 = (4x – 5)/3 2/(x ^ 2) = 1/3 (3(x – 1))/5 – (x – 3)/2 = (x – 8)/10 (x(x – 1))/4 – (2x ^ 2 + 1)/2 = – 3/4 * x ^ 2 – 0, 25(x + 2) II. (3x – 1)/(x + 2) = 2/3 II. 3x * (x + 2) = 0 II. (x ^ 2 + 2x + 6)/(x ^ 2) = 1 b) d) f) (x ^ 2 – 16)/(x – 4) = 0 III. (x – 4) – (2x – 9) = 0 I. (x ^ 2 – 4)/(x – 2) = 0 (3x – 1)/(x ^ 2 + 1) = 3/x x/2 = 8/x 1/(x – 1) + 2 = 0 (3(x – 11))/4 = (3(x + 1))/5 – (2(2x – 5))/11 (x + (4 – x)/3)/5 = (x – (x – 5)/5)/3 h)